2009
DOI: 10.1299/jmmp.3.199
|View full text |Cite
|
Sign up to set email alerts
|

Stress Histories of Yttria-Stabilized Zirconia and CoNiCrAlY Coatings during Thermal Spraying

Abstract: Thermal barrier coating (TBC) systems which are used for insulating the substrates of gas turbine blades from high temperature can be made by thermal spraying. The TBC system has residual stresses because of high temperature deposition and the thermal expansion mismatch in the system. In this study, how the residual stress occurs in TBC system was examined by both experimental measurement and FEM analysis. The Yttria-stabilized zirconia (YSZ) top coating was deposited by atmospheric plasma spraying (APS). CoNi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The temperature of coating and substrate was assumed to be identical. The physical values used in calculation were the same as previous paper [2]. Heat transfer coefficient depends on environmental flow.…”
Section: Experimental and Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature of coating and substrate was assumed to be identical. The physical values used in calculation were the same as previous paper [2]. Heat transfer coefficient depends on environmental flow.…”
Section: Experimental and Analytical Methodsmentioning
confidence: 99%
“…Residual stress plays an important role on delamination of TBC [1]. Authors [2] had investigated the arising mechanism of residual stress during thermal spraying by both measurement of temperatures and FEM stress analysis. In this paper, it was examined how the residual stress changed after thermal cycling and thermal aging.…”
Section: Introductionmentioning
confidence: 99%
“…Of course, such large stress could not be generated in the real coating because of the strength of the sprayed top coat. Furthermore, it was reported that the residual stress in the top coat after spraying was several tens of MPa by x-ray diffraction method ( Ref 13,20,21). Then, a consideration of stress relaxation due to crack generation was necessary for analysis of the deposition process of ceramic coatings.…”
Section: Elasto-plastic Analysismentioning
confidence: 99%